2018
DOI: 10.1103/physreva.97.013840
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of complete and continuous Wigner functions for discrete atomic systems

Abstract: We measure complete and continuous Wigner functions of a two-level cesium atom in both a nearly pure state and highly mixed states. We apply the method [T. Tilma et al., Phys. Rev. Lett. 117, 180401 (2016)] of strictly constructing continuous Wigner functions for qubit or spin systems. We find that the Wigner function of all pure states of a qubit has negative regions and the negativity completely vanishes when the purity of an arbitrary mixed state is less than 2 3 . We experimentally demonstrate these findin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…15 The series of simulations and experiments have proved practical usefulness of that new approach in the characterization of the discrete variable states in the continuous phase space. [16][17][18] In the first case such a Wigner function can exhibit negativity even for separable spin states 16 and in the latter case it was suggested that the Wigner function can serve as an indicator of the purity of single qubits. 17 This could imply that such observed negativity cannot uniquely be utilized in the characterization of the nonclassicality in the discrete domain.…”
Section: Introductionmentioning
confidence: 99%
“…15 The series of simulations and experiments have proved practical usefulness of that new approach in the characterization of the discrete variable states in the continuous phase space. [16][17][18] In the first case such a Wigner function can exhibit negativity even for separable spin states 16 and in the latter case it was suggested that the Wigner function can serve as an indicator of the purity of single qubits. 17 This could imply that such observed negativity cannot uniquely be utilized in the characterization of the nonclassicality in the discrete domain.…”
Section: Introductionmentioning
confidence: 99%
“…Two examples of this when measuring a single qubit can be found in recent works, ref. [134] and ref. [95], where in ref.…”
Section: Quantum Technologies In Phase Spacementioning
confidence: 99%
“…Finally, it is also worth mentioning that one of the advantages of using the WDF is that it can be reconstructed from experimental data. This reconstruction allows one to visualize the WDF for different physical systems such as states of trapped light 42 , states of the microwave field 43 , molecular vibrational states, electrons and ions states 44 46 , thermal states 47 , 48 or states of the spin systems 49 .…”
Section: Introductionmentioning
confidence: 99%